RANCANG BANGUN DECISION SUPPORT SYSTEM DISTRIBUSI PRODUK PADA INVENTORY ROUTING PROBLEM DENGAN PENDEKATAN HEURISTIK (Studi Kasus: Perusahaan Yakult) - Lisnawanty Lisnawanty (Universitas Bina Sarana Informatika, 2014)
The company is an organization that has a complexity of problems in managing the relationship between retailers and distributors to maintain product distribution process runs smoothly. Changes in market structure, products, and technologies of production continues to occur so that the effect is determined at the discretion of management. In this regard, the case of Inventory Routing Problem (IRP) often occurs in uncertainty in coordinating some activity distribution of products to a number of retailers. Product distribution system that is run without the basic result in reduced services to retailers. In other words, the distribution companies are not able to maintain service levels remain high. When the distribution system planned without basis in estimating demand so there are a number of retailers retailers that are not provided in time, the planning time horizon for the retailer must wait for resupply performed again at the next cycle. Determination of suboptimal solutions to some complex decision problems can face a bottleneck in terms of product quantity, time and cost can use a heuristic approach in building Decision Support System. Product Distribution DSS is a tool used to generate and produce suboptimal solutions in generating support for scheduling distribution. The decision resulting from the DSS Product Distribution is determining the time distribution will be made, determine many products that will be distributed, and determine the route to be traversed.Keyword: Inventory Routing Problem, heuristic, Decision Support System